Short Story, Translation and Cultural Transferences at the Colombian Illustrated Magazine El Gráfico (1925-1941) - Marín-Colorado, Paula Andrea (Íkala, Revista de Lenguaje y Cultura, 2018)
El Gráfico. Semanario Ilustrado (1910-1941), founded by typographers Alberto Sánchez and Abraham Cortés, was born as a magazine to provide illustrations, history, information, literature and varieties to its readers. In the second phase of the magazine (1925-1941), the journal had several changes that affected the way in which the short story literary genre was published in its pages, both written by foreign and Colombian correspondents. This paper will show the way in which El Gráfico became a mass media that reaffirmed the difference between the specialized and commercial circuits of the literary, and allowed to extend the repertoire for the Colombian short story. These processes occurred due to the relations with the French, Russian and Spanish literary system. The analysis proposed in the current study will be based on the relations between the press and literature, on the perspective of cultural transfers and on the translation studies.